OPTIMALISASI FORUM BAHTSUL MASAIL SEBAGAI MEDIA PENGUATAN MODERASI BERAGAMA SANTRI DI PONDOK PESANTREN NURUL HUDA - Muhammad Husni; Alfatun Nisak (Jurnal Pengabdian kepada Masyarakat, 2026)
This Community Service Program is based on the need of Islamic boarding schools to strengthen the moderate attitude of students in addressing differences of opinion in fiqh and improve the quality of scientific discussions in the Bahtsul Masail forum. Based on these conditions, this activity aims to provide an understanding of religious moderation and improve the ability of students to analyze fiqh issues critically and based on evidence. The program implementation methods include interactive training on the principles of tasamuh, tawazun, ta'adul, and i'tidal, case study discussions, and direct mentoring in Bahtsul Masail practices as a form of capacity building. The results of the activity show a significant increase in the understanding of the concept of religious moderation, the ability of students to formulate problems, the right to seek references to yellow books, and a moderate attitude during deliberations. Overall, this program is effective in strengthening the capacity of students and can be a model for pesantren-based empowerment. Keywords: Bahtsul Masail, religious moderation, Islamic boarding schools